2017
DOI: 10.5797/jnet.oa.2016-0072
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-inflation Anchoring Technique for Insertion of a Guiding Catheter in Acute Mechanical Thrombectomy

Abstract: Purpose: Anatomical factors involved in the difficulty of inserting a guiding catheter (GC) into the aortic arch include marked arteriosclerosis with severe vessel tortuosity and type-3/bovine aortic arches. For patients with such factors, we have inserted a balloon guiding catheter (BGC) using the balloon-inflation anchoring technique (BIAT). In this study, we introduce the BIAT, and examine its usefulness. Subjects and Methods:The subjects were 44 patients who underwent acute mechanical thrombectomy for occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…According to several studies, the route was changed, or the use of devices was devised in such patients. [3][4][5][6]11) Of patients with pc-LVO, the prognosis becomes unfavorable in approximately 90% when recanalization is not achieved. On the other hand, recent studies indicated that the endovascular treatment related effective recanalization rate was approximately 70%-80%, and that a favorable outcome was achieved in 30%-40%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several studies, the route was changed, or the use of devices was devised in such patients. [3][4][5][6]11) Of patients with pc-LVO, the prognosis becomes unfavorable in approximately 90% when recanalization is not achieved. On the other hand, recent studies indicated that the endovascular treatment related effective recanalization rate was approximately 70%-80%, and that a favorable outcome was achieved in 30%-40%.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) With respect to thrombectomy or the recanalization rate, favorable results have been consistently obtained, but we have often encountered patients in whom it was difficult to guide a guiding catheter into an occluded blood vessel, with an increase in the number of patients to be treated by this therapy. [3][4][5][6] Several studies reported that recanalization should be promptly performed to treat posterior circulation large vessel occlusion (pc-LVO), as indicated for the anterior circulation. 7,8) However, when selecting the transfemoral approach (TFA) for patients in whom an approach to the right vertebral artery (VA) is necessary, a specific interval is sometimes required until reaching due to the tortuosity of the aortic arch.…”
Section: Introductionmentioning
confidence: 99%
“…The inner catheter could be navigated to the peripheral artery with severe vessel tortuosity by dilating/anchoring a balloon of the balloon-guided catheter. 30) This technique could advance the 5MAX ACE more distally. The large aspiration catheter required a coaxial catheter for delivery to MCA.…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, the balloon is deflated and the BGC is advanced over the VDC ( Figure 3H). 26 In some situations, the hook of the VDC hampers its progression into the CCA. In these cases, the VDC can be used to catheterize the innominate or left CCA and an exchange-length Figure 1.…”
Section: Techniques For Challenging Supra-aortic Accessmentioning
confidence: 99%
“…If it is possible to advance the guidewire distal to this curve, we try to gently to insert the BGC in the take-off of the great vessel of interest and maximally inflate the BGC at the origin of the brachiocephalic trunk or left CCA to provide anchoring to support the distal navigation of the guidewire and VDC ( Figure 3F and G ). Finally, the balloon is deflated and the BGC is advanced over the VDC ( Figure 3H ) [ 26 ]. In some situations, the hook of the VDC hampers its progression into the CCA.…”
Section: Unfavorable Supra-aortic Accessmentioning
confidence: 99%